Improving Stability of Li-Ion Batteries by Means of Transition Metal Ions Trapping Separators. Issue 6 (29th March 2016) - Banerjee, Anjan; Ziv, Baruch; Shilina, Yuliya; Luski, Shalom; Aurbach, Doron; Halalay, Ion C.
Abstract : Transition metal ions dissolution from positive electrodes initiates a well-known degradation mechanism in Li-ion cells, which limits their operational life. Preventing its consequences should be considered as a breakthrough in the field. We show herein that trapping Mn ions by ion-chelating polymers placed in the inter-electrode space of cells with lithium manganate spinel and Li or graphite electrodes, and greatly improves their high temperature cycling performance. Mn cations trapping separators were fabricated in-house using a commercial resin consisting of iminodiacetic acid disodium salt functional groups on a styrene divinylbenzene polymeric matrix, either by their inclusion into a separator through a phase-inversion method or by coating onto a plain commercial separator. We determined and compared the surface and cross-section morphologies, electrolyte-uptake, porosity, ionic-conductivity, and electrochemical-stability of these separators with those of a baseline separator. LMO-Li cells containing phase-inversion separators had ∼15x less Mn on the Li-electrode than cells with the baseline separator, after 100 cycles at 55°C. LMO-graphite cells with phase-inversion separators had ∼6x less Mn on the graphite-electrode, after 100 cycles at 55°C than cells with the baseline-separator. Capacity losses after cycling at 55°C were 30% and 55%, respectively, for the cells with phase-inversion and baseline separators.